The effects of Kinesio tapes on facial swelling following bimaxillary orthognathic surgery in the supraclavicular region - Mohsen Golkar; Anita Taheri; Mostafa Alam; Yasin Asadi; Seied Omid Keyhan (SpringerOpen, 2023)
Abstract Background Several osteotomies are required for orthognathic surgery to reposition the jaws correctly. This study aimed to evaluate whether Kinesiotaping can reduce swelling, pain, and trismus following orthognathic surgery of the facial skull. Materials and methods The present study consists of two phases. In the split-mouth phase, 16 skeletal class III patients underwent Bimax Orthognathic surgery, and Kinesiological tape (KT) was applied on one half of the face. In the prospective case-control phase, 30 patients were divided into two groups. Kinesio tape was applied on both sides of the face of the Kinesio group, and pressure dressing and ice therapy were used for the second group. The tape was parallel to the lower border of the mandible along its entire length, tangent to the labial commissure area on the studied side. The tape was placed in place for 5 days. Edema was evaluated by measuring the distance from the menton to the lower edge of the tragus. The maximum mouth-opening trismus was evaluated, and the VAS index was used to evaluate pain. Results There was evidence of swelling reduction after KT; within the same study, differences between the left and right sides as well as for the same side were statistically significant (p < 0.001). As a result of tapping lymphatic Kinesio tape on the affected area, tension was reduced, and lymphatic circulation was restored. Blood and lymph microcirculation was improved, enabling the body to heal itself. Conclusion Kinesio tape reduced swelling after orthognathic surgery in a positive way. As a simple, non-traumatic, economical method, Kinesio taping seems promising.